Potential for knowledge in action? An analysis of Korean green energy related K3–12 curriculum and texts. Issue 6 (3rd July 2017) - Gress, Douglas R.; Shin, Jungyeop
Abstract: While understanding green energy development and what drives it are important, there is increasing consensus that sustainability transitions concerning usage need to be viewed in terms of the place specific contexts, including education, that critically mold them. In order to support sustainability transitions, information and knowledge building are not enough; knowledge must be turned into action. This research examines the potential efficacy of Korea's efforts in this regard via an analysis of K3–K12 geography education curriculum and texts vis-à-vis green energy content. There is scant disconnect between the curriculum and the texts analyzed, and, aside from the small shortcomings unearthed, analyses suggest that Korea is cogent of the ability of geography education and education for sustainable development to turn knowledge into action, thereby empowering civil society to drive its green energy transitions going forward.